144k views
4 votes
Hey guys please answer if you know​

Hey guys please answer if you know​-example-1

2 Answers

3 votes

Answer:

19

Explanation:

since value of both a+b and a*b are given

formula for a^2 + b^2 is (a+b)^2-2*a*b

Substituting those value,

a^2+b^2=5^2-2*3

i.e. 25-6

=19

User Granger
by
5.4k points
6 votes

Answer:

19

Explanation:

note that

(a + b)² = a² + b² + 2ab , that is

a² + b² + 2ab = (a + b)² ← subtract 2ab from both sides

a² + b² = (a + b)² - 2ab

= 5² - 2(3)

= 25 - 6

= 19

User Rajesh Rajaram
by
5.1k points